EVALUASI KEBIJAKAN EKONOMI SEKTOR INFORMAL: STUDI TERHADAP PELAKSANAAN PENATAAN DAN PENERTIBAN PEDAGANG KAKI LIMA DI KABUPATEN JEMBER - Asmuni .; Abdul Hakim (Universitas Tribhuwana Tunggadewi, 2014)
Policy problems of economic actors in formal sector are characterized by urban development in the formal economy sector on the one hand, while on the other hand the formal economic sector are not necessarily able to accommodate job seekers, giving rise to informal economic actors in the urban. This research is evaluation study about policy evaluation use formal evaluation prespective, ex-post evaluation, study of policy outcomes evaluation and find argument of term from stakeholders. The aim of this study include Knowing about the successful implementation of policy towards the informal sector economy (street vendors), knowing the actors involved in the informal sector economic policy (street vendors) in Jember and describe constraints in the implementation of policy towards the informal sector economy in Jember. The research method used qualitative research with data collected in-depth interviews, observation and documents. While the data analysis used an interactive model of data analysis.